“What a Girl Wants”: What Can We Learn From Animal Models of Female Sexual Motivation? - Guarraci, Fay A.; Frohardt, Russell J. (Frontiers in Behavioral Neuroscience, 2019)
Sexual motivation is notably different than other motivations such as hunger and thirst, because it lacks homeostatic drive. Sexual motivation poses no threat to physical well-being; individual survival is not at stake. Nevertheless, sexual motivation is a powerful drive and is critical for species survival. Understanding the complexity of sexual motivation has the potential to advance our understanding of other motivations, even pathological motivations, such as those associated with substance abuse. The study of motivation that is unique to females has often been neglected. A number of paradigms have been developed to investigate female sexual motivation beyond measuring only the lordosis reflex. Lordosis is a reflexive posture displayed by female mammals in response to male sexual stimulation to facilitate intromission. The lordosis reflex is essential, but studying the drive to mate is compromised in the absence of robust lordosis. Therefore, appetitive measures of sexual behavior (e.g., preferences, solicitation behaviors) are more specific and more sensitive indicators of sexual motivation than lordosis alone. Paradigms designed to study female sexual motivation often provide a female subject with the choice to interact with a sexually vigorous male or either a non-sexual partner (i.e., female, castrated male) or to remain alone. The study of appetitive measures of sexual motivation has elucidated the role of hormones in female sexual motivation, as well as the underlying neural pathways. The present review describes methods for studying female rats to advance our understanding of sexual motivation and sexual dysfunction.